Parameters contributing to waste generation at construction sites at Putrajaya - Abdul Moeis, Afif Azhan (2023)
Demanding of development and infrastructure in Malaysia result in the construction waste material been increase every year. Construction waste has a major impact on the environment if there is no proper management of construction waste from point of waste generated until point of waste disposal. Thus, it is important to identify factors influencing construction waste generated on the construction site. The study aims to identify parameters contributing to the construction waste generation at Putrajaya. Methodology of the study is document review and questionnaires. A total of 21 respondents within Putrajaya were selected for this research. The findings of the study will assist in the formulation of appropriate policy interventions in addressing the construction waste study predicting the factors influencing waste on site. The study determined the relative importance of index (RII) of the parameters contributing to waste generation at construction sites.